Information security 14th International Conference, ISC 2011, Xi'an, China, October 26-29, 2011. Proceedings - Lai, Xuejia; Zhou, Jianying; Li, Hui (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Information Security, ISC 2011, held in Xi'an, China, in October 2011. The 25 revised full papers were carefully reviewed and selected from 95 submissions. The papers are organized in topical sections on attacks; protocols; public-key cryptosystems; network security; software security; system security; database security; privacy; digital signatures.